Correlation of volumetric flow rate and skin blood flow with cold intolerance in digital replantation. Issue 51 (December 2017) - Zhao, Gang; Mi, Jingyi; Rui, Yongjun; Pan, Xiaoyun; Yao, Qun; Qiu, Yang
Abstract : Abstract: Cold intolerance is a common complication of digital replantation. The exact etiology is unclear, but it is considered to be multifactorial, including nonsurgical characteristics, vascular, and neurologic conditions. Blood flow may play a significant role in cold intolerance. This study was designed to evaluate the correlation of digital blood flow, including volumetric flow rate (VFR) and skin blood flow (SkBF), with cold intolerance in replanted fingers. A retrospective study was conducted among patients who underwent digital replantation between 2010 and 2013. Patients were selected into study cohort based on the inclusion criteria. Surgical data was collected on each patient, including age, sex, injury mechanism, amputation level, ischemia time, number of arteries repaired, and whether or not vascular crisis occurred. Patients were included as study cohort with both nerves repaired and without chronic disease. Cold intolerance was defined as a Cold Intolerance Symptom Severity (CISS) score over 30. The arterial flow velocity and caliber were measured by Color Doppler Ultrasound and the digital VFR was calculated. The SkBF was measured by Laser Speckle Imager. Both VFR and SkBF were calculated as a percentage of the contralateral fingers. Comparative study of surgical data and blood flow was performed between the patient with and without cold intolerance. Correlation between VFR and SkBF was also analyzed. A total of 93 patients met inclusion criteria for the study. Approximately, 42 patients were identified as having cold intolerance. Fingers that survived vascular crisis had a higher incidence of cold intolerance with a lower VFR and SkBF. The VFR was higher in 2-artery replantation, but the SkBF and incidence of cold intolerance did not differ significantly. No differences were found in age, sex, injury mechanism, amputation level, or ischemia time. Furthermore, no correlation was found between VFR and SkBF. Cold intolerance of digital replantation is associated with decreased SkBF and VFR in the replanted fingers, which survived vascular crisis. Further work will be focused on how vascular crisis cause the decreasing of SkBF and VFR and the increasing chance of cold intolerance.